2006
DOI: 10.1590/s0100-204x2006000400016
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de zinco via sementes e seu efeito na germinação, nutrição e desenvolvimento inicial do sorgo

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da aplicação de zinco em sementes de sorgo (Sorghum bicolor (L.) Moench) na nutrição, na germinação e no desenvolvimento inicial das plantas, em casa de vegetação. Utilizou-se delineamento inteiramente casualizado dos tratamentos, em esquema fatorial 2x5, duas cultivares de sorgo (BR 304 e BR 310) e cinco doses de Zn (0, 3,57, 7,14, 14,28 e 28,56 g de Zn por kg de sementes), com três repetições. Foram avaliadas as variáveis de germinação (tempo médio, médi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
2
7
0
15
Order By: Relevance
“…A similar result was found by Pessoa et al (2000), who observed an increase of heterogeneity and a delay in germination, and still a low initial development of plants when tested increasing doses of B in corn seeds. Yagi et al (2006) also verified that the application of zinc sulfate in sorghum seeds in a dose of 28.56 g.kg of seeds resulted in a minor percentage of germination. However, Tavares et al (2013) and Pletsch et al (2014) using in the recoating of seeds doses of commercial products that possessed 780 g.L -¹ of Zn in wheat seeds and 780 g.L -¹ of Zn in canola seeds, respectively, observed that the treatments provided benefits for the germination and initial establishment of plants.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…A similar result was found by Pessoa et al (2000), who observed an increase of heterogeneity and a delay in germination, and still a low initial development of plants when tested increasing doses of B in corn seeds. Yagi et al (2006) also verified that the application of zinc sulfate in sorghum seeds in a dose of 28.56 g.kg of seeds resulted in a minor percentage of germination. However, Tavares et al (2013) and Pletsch et al (2014) using in the recoating of seeds doses of commercial products that possessed 780 g.L -¹ of Zn in wheat seeds and 780 g.L -¹ of Zn in canola seeds, respectively, observed that the treatments provided benefits for the germination and initial establishment of plants.…”
Section: Resultssupporting
confidence: 55%
“…Meanwhile Yagi et al (2006) and Prado et al (2008) tested in sorghum seeds doses of zinc sulfate of 114.4 and of 28.56 g of Zn. kg -1 of seeds, respectively, and observed a significant decrease on the production of root dry mass.…”
Section: Resultsmentioning
confidence: 99%
“…Funguetto et al (2010) analyzed coating rice seeds with zinc, fungicide and a polymer and they also did not observe any changes in germination. However, Yagi et al (2006) noted a reduction in the percentage germination of sorghum seeds treated with zinc. Results from the accelerated aging test demonstrated that seeds treated both with product "A" and product "B" showed no significant difference when exposed to conditions of high temperature and relative humidity.…”
Section: Resultsmentioning
confidence: 96%
“…Da mesma forma o recobrimento de sementes de arroz irrigado com zinco não promoveu acréscimos na germinação e no vigor das sementes (OHSE et al, 2000). No entanto, em trabalho com sementes de sorgo tratadas com zinco (0,3,57,7,14,14,28 e 28,56 g de zinco por kg de sementes) tendo como fonte sulfato de zinco heptahidratado, foi constatado redução da percentagem de germinação com o aumento das doses (YAGI et al, 2006).…”
Section: Resultsunclassified
“…O Zn é requerido em pequenas quantidades, apresentando uma estreita faixa entre o efeito benéfico e a toxicidade (MALAVOLTA, 2006), explicando a redução na germinação a partir da dose de máxima eficiência. Tais resultados concordam com os encontrado por Yagi et al (2006) enéfico e a toxicidade (MALAVOLTA, 2006) A máxima área foliar (17,58 cm² planta…”
Section: Resultsunclassified